Pseudomonas aeruginosa alginate in cystic fibrosis sputum and the inflammatory response. - Pedersen, S S (1990)
Alginate, a viscous polysaccharide from mucoid Pseudomonas aeruginosa, may interfere with the host defenses in patients with cystic fibrosis and chronic P. aeruginosa lung infection. The alginate concentration in the sol phase of expectorated sputum was quantitated by a biochemical method and a newly developed enzyme-linked immunosorbent assay. There was a high degree of correlation between the methods, and the concentration of alginate ranged from 4 to 101 micrograms/ml with a median of 35.5 micrograms/ml when measured by enzyme-linked immunosorbent assay. Alginate could not be detected in the bronchial secretions from patients without P. aeruginosa infection. In vitro investigation of alginate did not show any activation of the alternative pathway of complement, as determined by a hemolytic kinetic assay and by testing for neutrophil chemotaxis. At a high concentration, P. aeruginosa alginate caused a slight activation of the classical pathway of complement. Alginate did not cause neutrophil chemotaxis by itself but was able to reduce the neutrophil chemotactic response to N-formylmethionylleucylphenylalanine and for zymosan-activated serum. P. aeruginosa and seaweed alginates were able to prime neutrophils for increased N-formylmethionylleucylphenylalanine-induced neutrophil oxidative burst, as determined by chemiluminescence. Because of its ability to prevent attraction of neutrophils to the site of infection, lack of complement activation, and ability to enhance neutrophil oxidative burst, alginate from P. aeruginosa may contribute to the persistence and pathogenesis of chronic P. aeruginosa infection in cystic fibrosis.